2018
DOI: 10.21776/ub.rjls.2018.005.03.5
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Compounds on Seaweed Eucheuma cottonii Extract as Antioxidant Candidate to Prevent Effects of Free Radical in Water Pollution

Abstract: Water pollution can make many problems such as, the incidence of disease and poisoning. Pollution in water can produce free radicals and it is can trigger of disease for aquatic organisms. There are some efforts that can be done to provide this problem, such as chemical compound that can reduce the reaction of free radicals. Antioxidants are one of the chemical compounds that can reduce the activity of free radicals. Eucheuma cottonii is the one of a seaweed that has many in antioxidant compounds, such as phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The principle of this assay is the ability of antioxidant compounds in a sample to bind free radicals and donor the hydrogen atom (Abdullah et al, 2020). The IC 50 values of some seaweed extracts have strong antioxidant activity, for instance, brown seaweed Sargassum polycystum ethanol extract (77.58±0.27 mg/L) and Padina minor ethanol extract (68.38±0.62 mg/L) (Manteu et al, 2018), green seaweed Caulerpa lentilifera ethanol extract (47.61 mg/L), Ulva lactuca ethanol extract (43.53 mg/L), and Halimeda opuntia ethanol extract (95.91 mg/L) (Nufus et al, 2017), and red seaweed G. gracilis methanol extract (59.01 mg/L) (Panjaitan & Yuliana, 2022) and E. cottonii methanol extract (39.93 mg/L) (Wulandari et al, 2018).…”
Section: Total Phenolic Content (Tpc) and Antioxidant Activity Of A F...mentioning
confidence: 99%
“…The principle of this assay is the ability of antioxidant compounds in a sample to bind free radicals and donor the hydrogen atom (Abdullah et al, 2020). The IC 50 values of some seaweed extracts have strong antioxidant activity, for instance, brown seaweed Sargassum polycystum ethanol extract (77.58±0.27 mg/L) and Padina minor ethanol extract (68.38±0.62 mg/L) (Manteu et al, 2018), green seaweed Caulerpa lentilifera ethanol extract (47.61 mg/L), Ulva lactuca ethanol extract (43.53 mg/L), and Halimeda opuntia ethanol extract (95.91 mg/L) (Nufus et al, 2017), and red seaweed G. gracilis methanol extract (59.01 mg/L) (Panjaitan & Yuliana, 2022) and E. cottonii methanol extract (39.93 mg/L) (Wulandari et al, 2018).…”
Section: Total Phenolic Content (Tpc) and Antioxidant Activity Of A F...mentioning
confidence: 99%
“…The ethanolic extraction from Eucheuma species was assessed to produce antioxidant potential properties (Bhuyar et al, 2020), and ethanol solvent exhibited the strongest value of antioxidant activity compared to distilled water (Prasasty et al, 2019). Furthermore, the extraction of E. cottonii using an alkaline solution had IC 50 value of 39,926 ppm, and was classified as very strong antioxidant activity (Wulandari et al, 2018).…”
Section: Figure 2 Antioxidant Activity Of Ethanol Extract Of E Cottoniimentioning
confidence: 99%
“…In addition, this species is able to synthesize significant amount of bioactive compounds which are potential to be developed. Previous studies have reported the valuable constituents of E. cottonii with a wide range of biological activities, such as antidiabetic (Prasasty et al, 2019), antibacterial (Bhuyar et al, 2020;Sukmawati, 2021), antioxidant to protect various diseases and stress (Muawanah et al, 2016;Yanuarti et al, 2017;Wulandari et al, 2018;Bangngalino and Badai, 2018;Sambodo, 2019;Ak and Türker, 2019). Moreover, macroalgae with phlorotannin content have been discovered to possess anti-inflammatory properties (Brown et al, 2014;Sudirman et al, 2018;Gutiérrez-Rodríguez et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Local ingredients in Indonesian coastal areas that can be used to produce jelly are Eucheuma cottonii, a red seaweed (Rhodophyceae) is the most cultivated seaweed in Indonesian costal area. Seaweed contains 12,42% crude fiber 8 and 2.6% protein which composed by 13 amino acids, with glutamate and aspartate contents as the majority 9 . Furthermore, Eucheuma cottonii contains vitamins, minerals, and phenolic compounds that have antioxidant properties 10 .…”
Section: Introductionmentioning
confidence: 99%